EXPLORING TOURISM IN THE CITY OF KUALA LUMPUR - Abdul Ghani Farinda; Ghazali Musa; Thinaranjeney Thirumoorthi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2008)
Kuala Lumpur, the capital city and the heartbeat of Malaysia, certainly has enough tourism products to keep tourists occupied while visiting the city. This study explores the hotel managers’ perception and opinion on tourism potentials of Kuala Lumpur as a tourism destination and looks at ways to develop the tourism products that are available there. Sixty hotel managers of hotels in the city area were interviewed. The results show that Kuala Lumpur lacks a number of important elements of a successful destination, and faces serious challenges such as lack of security, bad traffic, high cost and lack of cleanliness.